Gastric volvulus and tension gastrothorax secondary to spontaneous transdiaphragmatic intercostal hernia. Issue 1 (17th January 2022) - Bennet, Simon; Wang, Michael; Spiro, Calista; Tog, Chek
Abstract : Spontaneous transdiaphragmatic intercostal hernia is an extremely rare clinical entity featuring dual defects in the diaphragm and chest wall. We report on the case of a 59-year-old man who developed a large left-sided hernia secondary to the minor trauma of a coughing fit. The hernia subsequently enlarged over the course of 3 years until it contained the stomach, leading to a gastric volvulus and tension gastrothorax with secondary pneumothorax. A subtotal gastrectomy was performed with Roux-en-Y reconstruction, and he made a full recovery.